Co-design capacity development for the UN Ocean Decade - Zhang, Jialin; Ferse, Sebastian C. A.; Jennerjahn, Tim C.; Clausen, Alison; Lahl, Rebecca (Frontiers in Ocean Sustainability, 2024)
Effective ocean governance plays a critical role in managing and coordinating human activities, policies, and institutions to ensure the sustainable use and conservation of marine resources. Recognizing the importance of effective ocean governance, there is a growing awareness that new research approaches are needed to bring together actors from academia and non-academic sectors. Together they need to develop transformative science solutions for a more inclusive and equitable ocean governance system. Despite widespread interest in this collaborative endeavor, limited resources are available to provide structured support and training. This creates a pressing need to develop capacity and promote a shared understanding of collaborative research methodologies, such as co-design. In response to the need for capacity development in such methodologies, the “Co-design for the Ocean Decade” online training course was launched in collaboration with IOC-UNESCO in 2022, starting with a first pilot course in the African region. This first co-design training course under the Ocean Decade framework serves as a practical and research-backed model for future co-design training programs in other regions. The evaluation results of the course reveal its effectiveness in enhancing participants' knowledge and skills in key co-design areas, particularly in communication with stakeholders. The evaluation also highlights areas for improvement, such as the need for (i) monitoring and evaluation, and (ii) follow-up opportunities for practice and funding support. Based on the evaluation, for future research and training programs, we recommend: (1) to incorporate local and regional context into the training, (2) to integrate co-design training into ocean science education, and (3) to embed co-design of research and training into the capacity development program of the Ocean Decade.